Freedom from fear, freedom from want: an introduction to human security - Hanlon, Robert James (University of Toronto Press, 2016)
"Adopting an interdisciplinary perspective, Freedom from Fear, Freedom from Want is a brief introduction to human security, conflict, and development. The book analyzes such key human security issues as climate change, crimes against humanity, humanitarian intervention, international law, poverty, terrorism and transnational crime, among others. The authors encourage readers to critically assess emerging threats while evaluating potential mechanisms of deterrence such as conflict resolution, economic development, diplomacy, peacekeeping, international law, and restorative justice. Concise yet comprehensive, Freedom from Fear, Freedom from Want is an ideal text for human security courses."--